Perspektif Tentang Kedudukan Wanita Dalam Islam Dan Peran Sosial Wanita Dalam Islam - Agustina, Natasya; Siregar, Rini Wahyuni; Rangkuti, Nanda Wardatul Amalia (STAI Tebing Tinggi Deli, 2023)
In islam, there are preferences that said islam has discriminated between women and man, which is i tis gives a loss from woman. But in fact, there who don’t even know about the truth are judging how islam treating their woman. They gives a negative asume without knowing the reason and the advantages from the islam law. In fact, most of the muslim are fels comfortable and keep their activities like usual, without any worries and bridle from the law that have made.